Marco Giugni, Maria T. Grasso, (2019), Street Citizens. Protest Politics and Social Movement Activism in the Age of Globalization, Cambridge: Cambridge University Press - Gaetano Inglese (Coordinamento SIBA, 2020)
For Book Reviews abstract is not required